The Role of Investments in the Economic Growth of the Republic of Uzbekistan (Uzbekistan Open Conference, 2025)
This paper examines the role of investments in ensuring sustainable economic growth in the Republic of Uzbekistan. Special attention is paid to analyzing the state’s investment policy, as well as the dynamics and structure of domestic and foreign investments from 2020 to 2025. The paper explores the impact of investments on the development of priority sectors of the economy, including information technology, industry, agriculture, and infrastructure. It demonstrates that the active attraction of investments contributes to the modernization of production facilities, the creation of new jobs, the enhancement of the national economy’s competitiveness, and the acceleration of digitalization. In conclusion, it is stated that investment is a key factor in economic growth and a foundation for Uzbekistan’s further sustainable development.